PENGARUH GLOBALISASI TERHADAP NILAI-NILAI KEISLAMAN DALAM SISTEM PENDIDIKAN DI SEKOLAH ISLAM - Yus Hermansyah; Endang Rusyani; Mangun Rusnaya; Kusmiati, Elly; Badru Salam (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2023)
Globalization has become a phenomenon that has changed many aspects of life, including the education system in Islamic schools. This study aims to explore the influence of globalization on Islamic values in the education system in Islamic schools. The method used is qualitative research with a library research approach, which involves observation and documentation. The results of the study show that globalization has a positive and negative impact on Islamic values. On the one hand, globalization introduces technology and information that can improve the quality of education and expand the horizons of knowledge. On the other hand, challenges such as the influence of foreign cultures and materialism can threaten the integrity of Islamic values. This study recommends strategies to integrate Islamic values with global developments in a balanced manner so that education in Islamic schools remains relevant and based on Islamic principles.